KEWENANGAN PELAKSANA TUGAS MENTERI DALAM MENGAMBIL KEPUTUSAN DAN TINDAKAN YANG BERSIFAT STRATEGIS BERDASARKAN UNDANG - UNDANG NOMOR 30 TAHUN 2014 TENTANG ADMINISTRASI PEMERINTAHAN - Egi Dwitama, Sigit (Universitas Wiralodra, 2018)
One form of decree that is included in the scope of state administration is a Ministerial Decree, which is a decision determined and issued by a minister who is always concrete-individual in the form of administrative stipulations (beschikking). However, not all departments and/or government officials such as the Minister have the authority to form these decisions, because in forming decisions can be seen from the status of government officials as an example of the Ad Interim Minister who does not have the authority to issue strategic decisions. But different problems arise when there is Ad Interim of Energy and Mineral Resources Minister Luhut Binsar Pandjaitan issued Decree Number 6752 K / 70 / MEM / 2016 concerning Dissolution of Ad Hoc Organizational Units in the Ministry of Energy and Mineral Resources, which basically was a strategic decision. This study is a legal research using a normative juridical approach and descriptive analytical research specifications. The data used in this study are secondary data consisting of primary, secondary and tertiary legal materials. Data obtained through library studies and field research in the form of legislation, books, journals, and electronic media. The results of this study consist of 2 (two) analyzes, namely First, the position of the Acting Decree of the Minister of ESDM does not have legal validity because there is a disability when viewed from the aspect of authority, formation process, and the purpose of its establishment with legislation and AUPB and Second, towards legal validity which is not possessed by the Minister's decree executor, the decree becomes invalid and a mechanism is needed to cancel the decree.